Proposed Model for Navigating Digital Learning and Examining the Stress of EdTech - Shampa Rani Das; NZ Jhanjhi; Farzeen Asfaq; Haitham Alqahtani; Azeem Khan (International Journal of Engineering, Science and Information Technology, 2025)
The swift integration of information and communication technology (ICT) in education has introduced various tools for teaching, giving rise to concerns about technological stress (technostress) among teachers. While prior research has acknowledged the potential correlation between ICT and stress, a comprehensive investigation into the specific stressors affecting teachers is lacking. This exploratory research aimed to put forth the intricate relationship between educational technologies (EdTech) usage and stress among teaching professionals, shedding light on factors influencing technostress and its impact on teachers' individual lives. The comprehension of the wider ramifications associated with the integration of technologies in the field of education. The proposed model determines various stress reasons caused by digital learning platforms, which can help with the remedy measures based on the model findings. The methodology was explicit, multifaceted, and quantitative. Data from 152 teaching professionals were rigorously analyzed, with demographic questionnaire frequencies calculated using SPSS version 22.0 and hypotheses assessed using SmartPLS version 4.0. A Cronbach's alpha of 0.915 indicated that the questionnaire's queries exhibited high reliability. The findings revealed a robust correlation between stressors and their substantial effect on teachers' overall well-being, job satisfaction, and commitment to their respective organizations, emphasizing the significance of addressing technostress in the education sector.